FAKTOR YANG BERPENGARUH TERHADAP PREFERENSI IBU HAMIL MEMILIH RUMAH SAKIT IBU DAN ANAK ANDINI SEBAGAI TEMPAT BERSALIN DI KOTA PEKANBARU TAHUN 2018 - Melda Syafitri; Zulfan Saam; Oktavia Dewi; Mitra Mitra; Nurlisis Nurlisis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Andini Hospital mother and son as a private hospital that is experiencing strict competition, has a polyclinic of content and obstetrics very crowded in the visit, but the large number of visits in the polyclinics are not followed by The amount of inpatient obstetrics so that in find the DRILL RSIA Andini Low, This is related to the patient's satisfaction in the hospital maternity needs to be aware of the behaviour of consumers, the research aims to determine the factors affecting the decision to choose the place of the content of polyclinic patients and obstetrics in the hospital RSIA Andin. This research is a quantitative study with a crosssectional approach with 106 respondents This research is a quantitative study with a crosssectional approach with 106 respondents. The questionnaire that was used was valid and reliable. Research results known characteristics of majority patients aged 20-35 years, Working as Wiprivate with Education equivalent Academy/PT with salary above 3 million. A total of 19 people (24.7%) Stating no opt-out in the RSIA Andini. Variable facilities, earnings, and prices have a relationship with the decision to choose the place of delivery in RSIA Andini. While the age variable, work, doctor's service and medical service there is no relationship with the decision to choose the maternity place in RSIA Andini. Research advice for RSIA Andini is to add the number of nurses and midwives at the polclinics obstetrics for holidays and Weekand, doing three phases in setting the change or the price of the consumer, a more profound and specific customer survey to be able to make Find the right promotional media fibers conduct an evaluation of the facility materials. Keywords: Preference, decision-making, Content polyclinic